Un portale webGIS a supporto della viticoltura - Delluchi, Luca; Zorer, Roberto; Malacarne, Mario; Larcher, Roberto; Marinconz, Fabrizio (GEOmedia, 2009)
HarvAssist: a webGIS in support of grape harvesting HarvAssist is a website, created at the Edmund Mach – IASMA Foundation in collaboration with Cavit s.c., which aims to assist the winemakers in choosing the best time for grape harvest. The portal, developed only using open source software, is based on a geospatial database and it presents a simple web interface for managing and displaying the data. Finally a webGIS application allows to view the vineyards on maps, to retrieve the main chemical-analytical data and to receive projections of the ideal time for the harvest.